Observation of Self-Assemblage Behavior in African Nightcrawler (Eudrilus eugeniae) - Hayati, Rizki Rahma; Rahma, Hanifa; Sadana, Firnandez Ngariswara Vidsia; Kadang, Septiany Anugrah; Widarto, Tri Heru; Widayati, Kanthi Arum (Bogor Agricultural University, Indonesia, 2025)
Self-assemblage is a form of social behavior observed in some earthworm species, where individuals spontaneously group with conspecifics. This behavior has been previously documented in Eisenia fetida, an epigeic species widely used in vermiculture. However, the presence of similar behavior in E. eugeniae, another commonly used vermicomposting species, remains untested. This study aimed to investigate the self-assemblage behavior of E. eugeniae through a Y-tube choice test, evaluating individual preferences for conspecific presence. The experiment was conducted under controlled laboratory conditions using 30 replicates for both main (with conspecifics) and control (without conspecifics) treatments. Results showed a significant preference for the conspecific group in the main test (χ² = 6.5, p = 0.01), while no directional bias was observed in the control. However, decision-making time did not differ significantly between treatments (p = 0.63). These findings indicate that E. eugeniae displays active self-assemblage behavior. Further research is needed to identify the mechanisms underlying this behavior and its implications for applied soil ecology.